Solid-state lithium ion conductor
By employing high-temperature processes with water and/or steam contact during cooling, the method stabilizes solid lithium ion conductors, addressing degradation issues and ensuring high conductivity for battery applications.
Patent Information
- Application Number
- JP2023062069
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-29
- Filing Date
- 2023-04-06
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2041-03-05
AI Technical Summary
Solid lithium ion conductors are prone to degradation due to reactions with moisture and carbon dioxide in the air, leading to reduced conductivity and instability, especially in powder form, which complicates their manufacturing and usage in batteries.
A method involving high-temperature processes followed by contact with water and/or steam during cooling and quenching stages to produce solid lithium ion conductor materials, ensuring stability and maintaining conductivity.
The method produces stable, high-conductivity lithium ion conductor materials with minimal degradation, suitable for use in batteries, by avoiding adverse reactions and maintaining phase purity and optimal crystal modification.
Smart Images

Figure 0007608508000001 
Figure 0007608508000002 
Figure 0007608508000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid lithium ion conductor, a method for producing said solid lithium ion conductor, and uses thereof. [Background technology]
[0002] In recent years, lithium-ion based battery systems have become increasingly popular in battery technology. They are characterized in particular by high electrical energy density and expected long-term durability, allowing efficient battery construction. Here, the high chemical reactivity, the small mass of lithium ions as well as their high mobility play a central role. Therefore, the development of solid lithium-ion conductors is of great interest.
[0003] In solid-state batteries or storage batteries, both the electrodes and the electrolyte consist of solid materials. Solid-state batteries based on lithium ions as charge carriers are currently usually post-lithium ion batteries. Lithium ion batteries themselves are characterized by the use of graphite as the anode material. During charging of the battery, lithium ions can be stored in it. During discharging, they come out again from there. In parallel, electrons are absorbed in the graphite host system via an external circuit during charging and released again during discharging. In contrast, in the case of post-lithium ion batteries, elemental lithium is often used as the anode material. This allows a significantly higher energy storage density compared to graphite anodes. In these cases, lithium batteries also exist. In this case, the general advantage of solid-state batteries or storage batteries based on lithium is that they replace the liquid electrolyte, which is often flammable or toxic, and thus allows an improvement in the safety of lithium-based batteries.
[0004] Solid lithium ion conductors are usually incorporated into batteries in powder form, where they are either mixed with other battery components, such as active materials, or polymers and optionally sintered, or sintered or pressed with further additives, however, this often results in high contact resistances and only low conductivity is achieved in the sintered components.
[0005] For a long time, garnet-based solid lithium-ion conductor materials Li 7 La 3 M 2 O 12 (M=Zr, Sn, Hf), for example lithium lanthanum zirconium oxide (M=Zr) has been found to be stable in water (R.Murugan et al.,Angew.Chem.Int.Ed.Eng.46(2007)7778~7781; N.Imanishi,Solid Electrolytes for Aqueous Lithium Air Batteries,2014,215~234). However, in practical use, solid lithium ion conductors show the disadvantage that they react with moisture and carbon dioxide in the air already during preparation. For example, Yow et al. 6.6 La 3 Zr 1.6 Ta 0.4 O 12 (ZF Yow et al., Solid State Lonics 292(2016)122-129), and many other authors have reported other doped LLZO variants (Y. Jin et al., Journal of Power Sources 239(2013)326-331; Y. Wang et al., Journal of Power Sources 275(2015)612-620; C. Liu et al., Journal of Power Sources 282(2015)286-293; M. Nyman et al., Chem. Mater. 22(2010)5401-5410). + ) proton (H +) in great detail. The behavior of the materials was investigated in the form of pellets and in the form of powder and in dependence on time. In the case of the pellets used, only the surface layer was attacked, and the exchange after 7 days of storage in water was up to a maximum of 8.8%. In the case of the powder, a higher degree of exchange of up to 53.4% occurred under comparable conditions. In particular in the case of the powder, the said exchange can be somewhat reduced if a 1 M LiOH solution is used as the contact medium instead of pure water. Here, after 7 days of storage, Li + From H + Only 18.8% exchange occurs to LiOH, but this results in the presence of an undesirable LiOH phase in the powder. The exchange can be determined by analytical methods. + / H + A possible analytical method to measure the exchange is thermogravimetry. Alternatively, the proton accumulation in the material leads to a continuous broadening of the lattice parameters, so that the phenomenon can also be captured analytically by X-ray diffraction methods.
[0006] Li + / H + In the course of the exchange, lithium hydroxide is formed. In the subsequent reaction, the attacked LLZO material reacts with the CO present in the atmosphere, especially in the case of long-term storage in air. 2 It further reacts with Li 2 CO 3 This process has been described, for example, by Duan et al. for lithium garnets (H. Duan et al., Solid State Ionics 318(2018)45-53). Lithium carbonate can act as an insulating layer on the surface or between the crystallites, resulting in a highly enhanced contact resistance. However, the formation of lithium hydroxide is not a necessary requirement for the formation of lithium carbonate. Its formation can be achieved by the addition of CO to the atmosphere. 2 This can occur even under dry conditions if present.
[0007] Li + / H +Exchange-based degradation has dramatic consequences for the functionality of solid-state lithium-ion conductor materials. As molecular dynamics (MD) calculations show, the material transforms into a mixed ionic conductor, where Li + Ionic and proton conduction proceed in parallel, although they have different activation energies. Correspondingly, at low temperatures proton conductivity dominates, while at temperatures somewhat above 900 °C the proportion of lithium-ion conductivity is about 37%.
[0008] Water and CO from appropriately loaded solid lithium ion conductor materials 2 One possibility to remove it again is in principle a high-temperature treatment, for example as described in JP 2013-219017A. However, this requires relatively high temperatures of >650°C, which can already lead to loss of lithium by evaporation and, in the case of powders, sintering. Furthermore, JP 2013-219017A only demonstrates the high-temperature treatment with sintered pellets. Powders are only mentioned as a theoretical possibility and are not further characterized in terms of their properties. It is not disclosed or made clear whether or how the method can be carried out with powders.
[0009] In the publication by Yow et al. (2016, cited above), the authors reported that water and possibly additionally CO 2 They specify that the Ta-doped LLZO materials in contact with , both as sintered pellets and as powders, were reserved for further temperature treatment because of the expected high risk of decomposition and the associated large changes in conductivity. The risk of decomposition and the expected large changes in conductivity are also supported by thermodynamic considerations based on density functional theory calculations performed by Kang et al. (SGKang et al., J.Phys.Chem.C118(2014)17402-17406), which predict the decomposition of garnet-based solid ionic conductor materials according to the following reactions (1) and (2): 2Li 7 La 3M 2 O 12 +7H 2 O → 14LiOH+3La 2 O 3 +4MO 2 (M=Zr, Sn, Hf) (1) 2Li 7 La 3 M 2 O 12 +7CO 2 → 7Li 2 CO 3 +3La 2 O 3 +4MO 2 (M=Zr, Sn, Hf) (2)
[0010] In particular when using ionic conductors in powder form, the above-mentioned reactions (1) and (2) which occur on contact with water can cause problems during subsequent heating, since here a particularly high surface area is present. A lack of reproducibility of the results is associated with this, and in extreme cases these reactions and the subsequent depletion of lithium in the material can lead to a significant loss of conductivity.
[0011] In the case of lithium garnet, this does not necessarily result in a complete decomposition into the individual components, as calculated in the above-mentioned molecular dynamics (MD) calculations. However, it is necessary to at least obtain the lithium-poor phase, e.g., the La pyrochlore. 2 M 2 O 7 The formation of (M=Zr, Sn, Hf) often occurs, which leads to a significant impairment of lithium ion conductivity. In other cases, for example, solid lithium ion conductor materials based on lithium aluminum titanium phosphate (LATP: Li(Ti,Al) 2 (PO 4 ) 3 ), the crystalline phase may become amorphous at too high a temperature, which may result in a decrease in conductivity. In some cases, a deficiency of Al may occur in the crystalline phase, resulting in AlPO 4 The formation of may occur, which may also be associated with a loss of conductivity.
[0012] Variations of compositions that are less sensitive to reactions with the surrounding air have already been proposed (see, for example, JP 2017-061397A). However, it can be expected that lithium ion conductors with particularly high conductivity, due to the associated high lithium mobility, tend to react with air and in particular with the moisture contained therein. This applies in particular to materials with a high lithium content.
[0013] LATP is a compound that is similar to the hydroxyapatite that makes up our bones. 2 O 5 The orthophosphate compounds, i.e. salts of phosphoric acid, are similar to those formed completely from the cation by reaction with water and then (partially) neutralized in a further step with an alkaline solution / basic material. Such (often poorly soluble) salt compounds are known to incorporate a certain amount of water into the solvation shell of the cation or into the lattice structure of the crystal. However, the incorporation of water into the solvation shell or storage in the lattice structure is completely undesirable for the lithium ion conductor material according to the invention.
[0014] Furthermore, glasses with high alkali contents, especially Li contents, usually exhibit a high tendency for leaching of these ions from the glass matrix.
[0015] It is therefore foreseen that the use of water or water vapor as a forming or contacting medium for the production of solid lithium ion conductor materials based on phosphates, in particular lithium aluminum titanium phosphate LATP, is not considered.
[0016] Thus, the present invention has been developed completely away from conventional concepts and ideas from the prior art. [Prior art documents] [Patent documents]
[0017] [Patent Document 1] JP 2013-219017 A [Patent Document 2] Japanese Patent Application Laid-Open No. 2017-061397 [Non-Patent Document]
[0018] [Non-Patent Document 1] R.Murugan et al.,Angew.Chem.Int.Ed.Eng.46(2007)7778~7781 [Non-Patent Document 2] N.Imanishi, Solid Electrolytes for Aqueous Lithium Air Batteries,2014,215~234 [Non-Patent Document 3] Z.F.Yow et al.,Solid State lonics 292(2016)122~129 [Non-Patent Document 4] Y.Jin et al.,Journal of Power Sources 239(2013)326~331 [Non-Patent Document 5] Y.Wang et al., Journal of Power Sources 275(2015)612~620 [Non-Patent Document 6] C. Liu et al.,Journal of Power Sources 282(2015)286~293 [Non-Patent Document 7] M. Nyman et al.,Chem.Mater.22(2010)5401~5410 [Non-Patent Document 8] H.Duan et al., Solid State lonics 318(2018)45~53 [Non-Patent Document 9] S.G.Kang et al., J.Phys.Chem.C118(2014)17402~17406 [Summary of the Invention] [Problems to be Solved by the Invention]
[0019] The object of the present invention is to overcome the drawbacks from the prior art and to provide a solid lithium ion conductor material which is sufficiently water resistant to be manufacturable under the use of water and / or water vapor, but which nevertheless exhibits the required functionality as a lithium ion conductor in the form of a sufficiently high conductivity. [Means for solving the problem]
[0020] Description of the invention The above mentioned object is achieved according to the invention by means of the features of the independent claims. The dependent claims present preferred embodiments of the invention.
[0021] Surprisingly, it has been found that the production of solid lithium-ion conductor materials using water and / or water vapor as a medium in the high-temperature and / or low-temperature steps leads to particularly advantageous products of production. This is completely unexpected, since, starting from the experience described in the prior art, the processing of solid lithium-ion conductor materials in water as a medium would not only be considered disadvantageous, but also would not be feasible in terms of the stability of the material, the purity of the phases and the adjustment of the optimal crystal modification, as well as its functionality in the form of lithium-ion conductivity in general.
[0022] The present invention relates to a method for producing a solid lithium ion conductor material comprising the steps of: (1) providing a starting material for a solid-state lithium ion conductor material; (2) Using the starting material of the solid lithium ion conductor material, Melt method, Sintering method, · Ceramicization method, Calcination of the sol-gel precursor, or Bottom-up synthesis in pulsed reactors performing at least one high temperature step comprising: (3) cooling or quenching the resulting hot intermediate product; and (4) performing a cryogenic process in one or more comminuted stages to produce a powder; having In step (3) and / or step (4), the respective intermediate product is contacted with water and / or water vapor and subsequently dried; The present invention relates to the method.
[0023] In the following the method according to the invention will be explained in detail.
[0024] In the method of the present invention, the solid lithium ion conductor material is prepared in multiple steps.
[0025] In step (1) of the method according to the invention, a starting material for a solid lithium ion conductor material is provided. The invention is not further limited in this respect, in so far as the solid lithium ion conductor material can be produced via melting, sintering, ceramming, calcination of a sol-gel precursor or bottom-up synthesis in a pulsed reactor. Such solid lithium ion conductor materials are known to those skilled in the art. These are, for example, solid lithium ion conductor materials based on the NASICON structure. The NASICON structure is a corner-sharing PO 4 Tetrahedrons and octahedra, e.g. TiO 6 Octahedron or GeO 6 The NaSICON structure allows easy movement of Li ions through the crystal lattice. Solid lithium ion conductor materials based on the NASICON structure are preferably selected from materials based on lithium aluminum titanium phosphate (LATP) and / or materials based on lithium aluminum germanium phosphate (LAGP).
[0026] Other solid lithium ion conductor materials that can be produced are based on garnet structures. These are preferably selected from materials based on lithium lanthanum zirconium oxide (LLZO).
[0027] The term "based on", for example based on lithium aluminum titanium phosphate (LATP), means that there is a respectively known basic structure, but there may be deviations from the basic structure known from the prior art. These may be, for example, additional doping with other elements, such as tantalum, aluminum, niobium, zirconium, gallium, yttrium, silicon, germanium, tellurium, chromium, iron, scandium, boron, rare earths, halides, alkali metals and / or alkaline earth metals. These dopings are known from the prior art. The above term therefore includes all compounds falling within the general generic concept.
[0028] In the method according to the invention, firstly the starting materials for the solid lithium-ion conductor material are prepared, i.e. the corresponding oxides, hydroxides, carbonates, sulfates or further salts are provided.
[0029] In the case of starting materials for solid lithium-ion conductor materials crystallizing according to the garnet structure, a material composition is preferably selected which has an excess of lithium compared to the stoichiometric composition, preferably 2% to 100%, particularly preferably 2% to 25%, in moles relative to the formula units of the crystal of the stoichiometric ratio.
[0030] In the case of solid lithium-ion conductor materials based on the NASICON structure, the method according to the invention can usually be carried out without added lithium, using unaltered raw starting materials, i.e. without an excess of Li.
[0031] The prepared starting material is then subjected in step (2) to a high temperature process including melting, sintering, ceramming, calcination of a sol-gel precursor, or bottom-up synthesis in a pulsed reactor.
[0032] The high temperature step may for example comprise melting of the starting materials. Alternatively, sintering, in particular solid-state sintering, can be used at temperatures below the melting temperature of the starting materials.
[0033] Ceramization is advantageously carried out as an intermediate step, which is optional, for example in the case of LATP.
[0034] A further high-temperature process is the calcination of the sol-gel precursor. In this case, the precursor is first produced in a sol-gel process, usually by wet-chemical methods at relatively low temperatures. In the sol-gel process, after removal of the solvent by drying, a precursor is obtained, which is converted into the desired material by calcination as a high-temperature process step.
[0035] Bottom-up synthesis in pulse reactors is also a high-temperature process known to those skilled in the art, since the synthesis reaction takes place in a pulsed hot gas stream, in which case exhaust gases from combustion reactions are generally used.
[0036] The overall high-temperature process may comprise one or more stages / part steps. Said high-temperature process or processes may be followed by one or more post-treatment steps, which are also high-temperature processes. Said high-temperature processes may each follow one another directly without any other intermediate steps, i.e. one or more high-temperature processes are carried out one after the other. Between the individual high-temperature processes, the intermediate product may each be cooled to room temperature. However, this is not necessary in all cases. Post-treatment, for example in the form of heat treatment, preferably in a furnace, with defined temperature-time programs for heating, holding and cooling, each optionally with intermediate holding steps, serves to adjust the desired crystal modification and / or crystallite size.
[0037] Overall, the high temperature process serves to produce the desired multi-component system and may include, for example, the following methods: a melting process in which two or more prepared starting materials are melted into a glass and, by suitable cooling and optionally after cooling, the glass is converted into a glass ceramic; carrying out further ceramic steps in the form of heat treatment, for example in a furnace, with defined temperature-time programs for heating, holding and cooling, each possibly with intermediate steps, in order to adjust the desired crystal modification and / or crystallite size; A sintering process for sintering two or more prepared starting materials within the scope of a solid-state reaction at an elevated temperature but below the melting temperature of the starting materials; Calcination of a sol-gel precursor, including calcination of a precursor produced in a sol-gel process, or Bottom-up synthesis in a pulse reactor and optional subsequent post-calcination to tailor the crystal modification and / or crystallite size.
[0038] Following the heating step according to step (2) of the method, in step (3) the hot intermediate product obtained is cooled or quenched. In this case, the intermediate product can be contacted with water and / or water vapor, followed by drying. This cooling or quenching can also be performed without water or water vapor. In general, the cooling or quenching can be, for example, natural cooling to room temperature, or a controlled cooling or quenching. The hot intermediate product can be cooled, for example, by contacting it with cold water, cold air, or a cold, thermally conductive material, followed by drying. The cooling or quenching can also be performed by other techniques known to those skilled in the art.
[0039] According to a preferred embodiment of the present invention, in step (3), the hot intermediate product obtained is cooled or quenched while simultaneously being broken down into particles. The breaking down includes, for example, atomizing the hot intermediate product into droplets or singulating the hot intermediate product into particles, for example coarse particles. During the implementation of step (3), the hot intermediate product can be contacted with water and / or water vapor. Thus, according to this embodiment, step (3) is a hot compacting process.
[0040] Stage (3) as a hot shaping process in the form of spraying or fritting serves to cool or quench the material to form an intermediate product with as few crystalline phases as possible and correspondingly as high a proportion of amorphous or glassy phase as possible, thereby preventing the risk of uncontrolled formation of undesired crystalline phases due to uncontrolled temperature-time profiles during cooling.
[0041] Furthermore, it is advantageous if step (3) as a hot forming process results in an intermediate product which proves to be particularly conveniently handleable in a subsequent subdivision process: for example, particles formed in a spraying or fritting process or glass ribbons produced by cooling in a rolling mill (alternative cooling or quenching methods without contact with water) are clearly better subdivisionable than large monolithic blocks.
[0042] According to a preferred embodiment, the resulting hot, preferably still liquid, intermediate product is cooled or quenched in step (3) and simultaneously broken down and contacted with water and / or water vapor. Particularly preferably, this is achieved by atomizing the liquid intermediate product into droplets using the spray medium water. The spray medium in the form of water can be introduced as a water jet, for example in a water chute or via a nozzle.
[0043] In the case of the water chute, the resulting liquid intermediate product produced via the melting step according to step (2) of the method according to the invention is conducted in a jet via the melt feed to a "water chute". The water chute serves to quench or cool the droplets in water. When the melt hits the flowing water film, the melt jet is broken down into fine droplets.
[0044] The viscosity of the liquid intermediate used may be, for example, in the range of 0.1 to 1 dPa at temperatures of 1450° C. to 1600° C. In the water chute, the water flows at a high velocity, for example 0.1 to 3 m 3 / min, particularly preferably 1.7 m 3 / min throughput, flowing over an inclined channel, preferably a channel of special steel. In this case, the inclination angle of the water chute can be adjusted as desired, preferably from 10 to 75°, particularly preferably 45°.
[0045] In the case of a water chute, it is preferred that at the bottom the entire wall of the channel is covered with a water film. The generated droplets form a steam cushion by contact with the water film, which prevents further contact of the droplets with water. A water chute differs from a water bath in that the diameter of the material droplets can be adjusted in a targeted manner using the water chute. Preference is given to the interval of the melt feed into the water chute, the inclination angle of the water chute, for example in the range of 10-75°, preferably 45°, and the adjusted water flow rate, for example 0.1-3 m. 3 / min range, preferably 1.7m 3 Depending on the speed / min the diameter of the droplets can be adjusted. Preferably the diameter of the droplets is less than 20 mm, such as 19.99 mm or less, preferably less than 10 mm, such as 9.99 mm or less, sometimes preferably in the range of 0.5 to 1 mm.
[0046] Thus, the droplets do not come into direct contact with the material of the water chute below. They move, for example, on their way to a collector or are swept away by a water jet and are collected or collected in a suitable collection vessel. The droplets solidify immediately after the melt jet breaks off into droplets or during their flight travel. On impact in the collection vessel, they are already solid but still very hot (>700°C) and therefore above the ceramicization temperature, which is usually measured in a DTA measurement (differential thermal analysis). Preferably, the collection vessel can be cooled. Thereby, the solid particles are cooled very quickly during immersion and no or only little crystallization occurs. Thus, almost completely amorphous glass (ceramic) particles are obtained.
[0047] The use of water chutes has great advantages: for example, the hot liquid intermediate product obtained from the melting process can be directly broken down into particles without intermediate steps. The size of the particles can be adjusted as desired, so that the number of additional break-down steps in the subsequent low-temperature process and the energy required for this can be significantly reduced. Overall, this simplifies the process and makes it more economical. This is particularly important in the case of large-scale production.
[0048] Alternatively, a chute may not be used, but rather a jet of water may be generated, for example by means of a nozzle, and directed directly at the jet of molten liquid of the intermediate product.
[0049] By using water as the atomizing medium, the droplets only come into direct contact with the water to a small extent, since a cushion of water vapor catches them. The fact that a cushion of vapor exists between the two media as soon as the water and the melt collide with each other serves to prevent, or at least keep as small as possible, any possible leaching of Li-ions at this point in the process.
[0050] Quenching the glass melt in water, for example in a water chute, is already known from the prior art but has been used so far in completely different fields, for example in the production of granules of blast furnace slag or in the case of polymers, but this technique has not been used so far for lithium-ion conductor materials.
[0051] For example, quenching of the melt is used for the production of granules from blast furnace slag occurring as a by-product in the steel industry (Journal of Non Cryst. Solids 499 (2018) 344-349 or EP 1284299). In this case, the liquid slag is rapidly cooled and granulated using a jet of water, which leads to a vitreous solidification and simultaneous fragmentation. In a completely unexpected manner and departing from the usual ideas and concepts from the prior art, this approach can be used to produce lithium-ion conductors, without the expected disadvantageous washout of Li and thus the associated adverse effects on ionic conductivity. No other adverse effects were identified due to the use of water.
[0052] The usual method of producing lithium ion conductors via melting involves rapid cooling via contact with cold, thermally well-conducting, e.g. metallic, materials, e.g. rollers, moulds and the like. However, the use of metallic materials carries the risk of contamination of the ion-conducting material, which may adversely affect the electrical (electronic) conductivity. This means that the electrical (electronic) conductivity in the ion-conducting material should be as low as possible. Wear of the metal may increase this to an undesirable degree. In the use of the battery, the current should not flow within the battery, but through an external circuit, i.e. provided to the consumer in the form of an appliance or installation. There, ionic conduction should predominate.
[0053] According to the invention, therefore, quenching and comminution using water, in particular using a jet of water, for example brought about via a spray nozzle or directed in a water chute or the like, is particularly preferred for the production of lithium-ion conductors.
[0054] If the intermediate product has been contacted with water and / or water vapor in step (3), the intermediate product is preferably dried, which can be carried out in a manner known to those skilled in the art.
[0055] It has proved to be particularly advantageous if the cooling or quenching process of the hot intermediate product in step (3) is preferably carried out in water and / or steam or with water and / or steam while shaping. The use of water and / or steam has a number of advantages: the water jet or steam can be used as a continuous melt stream after the melt is obtained and serves as a medium for atomizing the melt into fine particles immediately after it leaves the melting crucible. The formation of these particles facilitates the subsequent rapid cooling and subsequent further fragmentation steps due to the increased surface area. After atomization, it is advantageous to transfer the particles into water to achieve the fastest possible cooling and thus hardening. Furthermore, water is particularly economical and therefore easy to use in mass production.
[0056] In the method according to the invention, the high-temperature step and the shaping step during the cooling or quenching process after the high-temperature step are preferably selected so as to optimally prepare for the subsequent low-temperature process steps and to have as good a but not as bad an effect on the properties of the product as possible. By "optimally prepare" it is understood here that the high-temperature step or steps are carried out in such a way that individual steps of the series of low-temperature steps can be omitted or simplified more or less significantly. This relates, for example, to a reduction in the necessary grinding time or the introduced grinding energy. For example, this can be achieved by skillful flinging or spraying of the melt, which results in sufficiently small fritted particles that can be directly fed as feed material to the fine grinding step without the need for a separate, possibly multi-stage, coarse comminution step, for example by breaking in a jaw crusher and subsequent coarse comminution in a ball mill or disk mill. A further possibility is to introduce tension, for example in the glassy material by particularly fast cooling, which makes it easier to break the feed material in the subsequent comminution step. This process is particularly advantageous according to the invention.
[0057] Following step (3) of the method according to the invention, in any intermediate step before step (4), the cooled intermediate product can be subjected to a heat treatment, for example in a furnace. For this, the heat treatment is carried out using a defined temperature-time program for heating, holding and cooling, each with an optional intermediate holding step, in order to adjust the desired crystal structure. The defined temperature-time program depends, inter alia, on the selected starting material, its amount, the resulting bulk material, the desired proportion and type of crystalline phases, the crystal size, the texture / microstructure of the starting material in the respective applied form (e.g. fritted particles, ribbons, etc.) and the geometrical size and homogeneity. The minimum temperature required for the formation of the desired crystalline phase results, for example, from the position of the crystallization peak, determined using differential thermal analysis. In addition to the temperature-time program, the atmosphere selected during the heat treatment also plays a role, i.e. the process gas used in this case (e.g. air, oxygen, inert gas, e.g. nitrogen or argon, decarbonized air) as well as the adjusted humidity. For this, the skilled person can use knowledge from the prior art. The heat treatment can be, for example, calcination, ceramization, sintering or another high-temperature process.
[0058] Additional heat treatment steps (repetition of any intermediate steps) can be carried out to adjust the proportion of the desired crystalline phases and the phase composition, depending on the individual case.
[0059] Besides the adjustment of the desired crystalline phase proportions and phase composition, a further advantage of the optional intermediate stage is that the heat treatment largely drives off residual water still present from the material.
[0060] The intermediate product obtained after step (3) or after carrying out any intermediate steps but before carrying out step (4) can, for example, be solidified in the glass or glass ceramic state, i.e. be X-ray amorphous to a large extent. The exact crystalline proportion and possibly the proportion of different crystalline phases can be adjusted, for example, via the cooling history, i.e. the selection of the process conditions. Depending on the adjustment of the process conditions, the intermediate product can thus have a more or less high proportion of crystalline phases.
[0061] Depending on the combination of the high temperature step and the cooling process, a crude product is produced as an intermediate stage in the form of agglomerates, ribbons, frits, granules or coarse particles. The particles often have cracks or at least internal stresses, which is particularly advantageous for the subsequent low temperature process, because this allows the particles to be subdivided more easily and with less grinding energy.
[0062] The process steps of the high-temperature process may follow one another directly, preferably without additional process steps.
[0063] Step (3), optionally followed by any intermediate step in the form of a heat treatment, is followed by a low-temperature process according to step (4), which also includes one or more steps in the form of a comminution step to produce a powder in its practical use form.
[0064] In a low temperature process in step (4), a powder is produced from the intermediate product obtained in one or more comminution steps, preferably by contacting with water and / or water vapor in at least one comminution step, followed by converting the crude product into a powder form having the desired particle size and particle size distribution in one or more comminution steps.
[0065] Preferably, the low temperature process comprises one or more of the following steps: Subdivision using hammers and chisels, Compression using roll crushers and / or jaw crushers, Comminution using ball mills and / or hammer mills, Comminution using ball mills, impact mills and / or planetary mills, Comminuted using a disc vibratory mill, Comminution using counter jet mills, spiral jet mills and / or steam jet mills; comminution using dry and / or wet ball mills, Comminution using a dry mixer ball mill and / or a wet mixer ball mill, Comminution by high energy comminution in a high speed rotor ball mill.
[0066] In this connection, it should be mentioned that mills can be classified in three types: by type of drive, by product, and by function. The mills mentioned above are classified here by function.
[0067] In the prior art, the low-temperature process, i.e. the comminution stage, is usually carried out under dry conditions, which is not always rational. Now, in an unexpected way, wet comminution of solid lithium-ion conductor materials to suitable small particle sizes is possible. For example, comminution to particle sizes in the single-digit μm or sub-μm range can often only be carried out in a comminution step in a liquid medium, for example in an agitator ball mill. This is now possible for solid lithium-ion conductor materials according to the present invention. Furthermore, from an economic point of view, the use of a liquid medium, for example water, is particularly rational. Alternatively, a counter jet mill with superheated steam as process gas can also be used.
[0068] Therefore, the use of water as a process medium in low-temperature processes for producing solid lithium-ion conductors in the form of powder use, whether in the form of liquid or as steam, especially superheated steam, is very advantageous for achieving the desired particle size. Moreover, water and steam do not present problems in handling, are non-toxic, can be used in large quantities in mass production applications, and are particularly cheap and reusable from an economic point of view. Furthermore, the use of water allows for very small particle sizes to be adjusted, which is not possible or very difficult to replace in other ways. Therefore, the use of water and / or steam in low-temperature processes is advantageous and usually even preferred.
[0069] If the product has been brought into contact with water and / or water vapor in at least one comminution step, then drying is preferably carried out, with a proportion of residual water remaining in the dried product. As a drying method, for example, freeze-drying can be used. This is carried out in particular during wet grinding in condensed water. In the case of grinding with water vapor, other drying methods are preferably used. Freeze-drying has the advantage that it allows drying in a very gentle manner, in particular at low temperatures, which is therefore particularly advantageous for the production of the solid lithium-ion conductor material according to the invention. Freeze-drying is preferably used only after fine grinding. In this case, the products produced have a high specific surface area (>0.5 m 2 / g), the small particles can now interact with each other and even form agglomerates or aggregates that are difficult to break apart, especially when using simple thermal drying. Freeze drying combats this phenomenon. Other drying methods, preferably gentle drying methods, are also possible.
[0070] Step (4) can be followed, preferably without intermediate steps, directly by step (5), by which a proportion of the remaining residual water can be removed by a temperature treatment. This step (5) is an optional step and is not necessary if a corresponding process is carried out, for example in the case of fritting in water and subsequent dry grinding. Step (5) comprises carrying out a temperature treatment at a temperature of at least 200° C. to remove the residual water remaining in the product obtained, said temperature treatment being carried out by the addition of CO 2 It is carried out in the absence of an ambient atmosphere, resulting in a powder of solid lithium ion conductor material having a moisture content of less than 1.0 wt. %.
[0071] If the solid ionically conductive material is first loaded with water during the corresponding preceding process step, it has been found that this water can be removed again without significant damage to the material and its function if the water-loaded intermediate product is treated in a temperature treatment step defined by optional step (5) at at least 200°C, preferably at least 300°C, preferably at least 400°C, more preferably at least 500°C. The upper limit for the temperature depends largely on the basic material and on the respective transformations. Furthermore, the efficiency of expelling the strongly bound water also increases with increasing temperature. However, above 400-500°C there is a risk of problems with sintering, in which undesirable aggregates are formed or functional structural components decompose. Depending on the individual case, the temperatures may be exceeded.
[0072] The goal of the method of the present invention is in any case to ensure that the particles of the powder have a size of at least 10 -5 The powder is made of a lithium ion conducting material having a conductivity of 0.05 S / cm and has a water content of <1.0% by weight, preferably 0.99% by weight or less, despite contact with liquid water or water in vapor form during manufacture.
[0073] The process steps of the low temperature process may follow one another directly, preferably without additional process steps.
[0074] The method according to the invention is also suitable for the production of solid lithium-ion conductor materials in mass production, whereby it is possible, especially from an economic point of view, to provide large quantities of solid lithium-ion conductor materials in powder form, when inexpensive processes are used for the production along the entire process chain, where the use of water and / or water vapor is particularly advantageous.
[0075] The subject of the present invention is also a solid lithium-ion conductor material in powder form obtainable by the above-mentioned process of the invention.
[0076] In the present invention, the term "solid lithium ion conductor material" refers to a material that is made of a lithium ion conductive material and has a thermal conductivity of at least 10 at room temperature. -5It is understood to be a material having an ionic conductivity of 100 S / cm.
[0077] Suitable materials for the method according to the invention are ion conductors based on garnets, for example those described in DE102014100684B4, glass ceramics with NaSICon structure, for example LATP, LAGP (for example DE102018102387B3), but also ion conductors with perovskite structure, for example lithium lanthanum titanate, or amorphous ion conductors, for example borate or phosphate glasses, are conceivable. The method according to the invention is also suitable for producing Li-ion conducting electrode materials, for example lithium vanadium phosphate.
[0078] Besides high electrical conductivity, the solid lithium ion conductor material of the present invention is characterized in particular by good sinterability even at relatively low temperatures. For example, according to the present invention, the particularly small particle size that can be provided by wet grinding leads to high sintering activity.
[0079] The invention further relates to the use of the solid lithium ion conductor material in powder form in a battery or accumulator, preferably a lithium battery or lithium accumulator, in particular as a separator, cathode, anode or solid electrolyte.
[0080] The lithium ion conductive powder material produced by contact with water (steam) according to the invention can be used alone or together with other battery materials, for example sintered into a purely inorganic ceramic membrane or incorporated as electrolyte, as filler, into a polymer electrolyte or polyelectrolyte, into a rechargeable lithium ion battery, in particular into a solid-state lithium ion battery (all-solid-state battery (ASSB)). On the one hand, it can be used as a separator, i.e. introduced between the electrodes, protecting them from undesired short circuits and thus ensuring the functionality of the entire system. For this purpose, the corresponding composite can be incorporated into the battery as a solid electrolyte, either by being applied as a layer on one or both electrodes or as a self-supporting membrane. On the other hand, it can be sintered or compounded with the electrode material, i.e. in this case the solid electrolyte provides for the transport of the relevant charge carriers (lithium ions and electrons) towards or away from the electrode material and the conductive electrode, depending on whether the battery is now being discharged or charged.
[0081] The present invention is explained in more detail below by means of examples, without however being limited thereto. [Brief description of the drawings]
[0082] [Figure 1] FIG. 2 is a diagram showing the obtained X-ray diffraction pattern (Example 1). [Diagram 2] FIG. 1 shows the obtained X-ray diffraction pattern (Example 2). [Diagram 3] FIG. 1 shows the obtained X-ray diffraction pattern (Example 3). EXAMPLES
[0083] Example 1 Example of the preparation of a solid lithium ion conductor material that crystallizes based on the garnet structure, on the example of lithium lanthanum zirconium oxide (LLZO) as a powder with little water.
[0084] The preparation can be carried out by the method according to the invention by a high-temperature process in the form of a melting process, natural cooling of the melt, coarse comminution under dry conditions, wet grinding in water with subsequent freeze-drying and drying N 2 This is done through a temperature treatment at 700°C under atmospheric conditions.
[0085] A low water LLZO powder according to Example 1 was prepared as described below:
[0086] a) Preparation of Nb-doped LLZO melt as hot intermediate product So-called skull crucibles are used, as described, for example, in DE 19939782 C1. In the skull technique, a water-cooled crucible is used, and during melting, a colder protective layer is formed from the material to be melted. The crucible material therefore does not melt during the melting process. The input of energy into the melt is realized by means of high-frequency coupling via an encircling induction coil into the molten material. The condition in this case is a sufficient conductivity of the melt, which in the case of a lithium garnet melt is brought about by a high lithium content. Lithium vapor is produced during the melting process, which can be easily corrected by an excess of lithium. For this purpose, a small excess of lithium is used.
[0087] In the example, La 2 O 3 , Li 2 CO 3 , Nb 2 O 5 and ZrO 2 is used as a mixture with the formula Li 7+x La 3 Zr 1.5 Nb 0.5 O 12Nb-doped lithium lanthanum zirconate with 100% Nb was produced. The raw materials were mixed according to the composition and charged into an open skull crucible. To achieve a certain minimum conductivity, the mixture had to be preheated first. For this purpose, burner heating was used. After reaching the coupling temperature, further heating and homogenization of the melt was achieved by high frequency coupling via an induction coil. To improve homogenization of the melt, it was stirred with a water-cooled stirrer.
[0088] b) Preparation of agglomerated blocks from Nb-doped LLZO as a cold intermediate. The LLZO melt produced in the skull crucible is directly solidified by switching off the high frequency coupling via the surrounding induction coil, and the cooled intermediate product is produced as a solid block.
[0089] c) Omission of ceramicization If the melt is directly solidified, the LLZO material exhibits spontaneous crystallization, thus eliminating the need for a subsequent ceramization process.
[0090] d) Production of fine powders loaded with residual water from Nb-doped LLZO The following comminution steps are carried out to produce a powder, still loaded with residual water, from the bulk block of Nb-doped LLZO material:
[0091] First, the agglomerated blocks are broken into smaller pieces using hammers and chisels. These are then fed in one or more passes through a jaw crusher until the pieces are a maximum of 10 mm in their longest dimension. These are then crushed in a Fritsch Pulverisette 13 classic disc mill. 99 The coarse powder is then ground to a particle size of <100 μm. 99 Sieve to <63 μm.
[0092] 1 kg of coarsely ground Nb-doped LLZO powder with a particle size of <63 μm is dispersed as free of agglomerates as possible in 2.33 L of water using a dissolver (disk agitator). The suspension is then charged into the reservoir of an agitator ball mill and ground for 2.5 h using a grinding chamber equipped with a pin mill agitator, utilizing the multi-pass method. The grinding chamber is then filled with ZrO 2 The milling balls, consisting of 10 ...
[0093] After grinding, the ground slurry is subjected to drying in a freeze dryer. For this, it is first poured over a large area into a product tray prepared for its intended use and frozen at a temperature of -30°C. A vacuum corresponding to the value required for the sublimation of the medium is then applied (<6.11 mbar for water). By subsequently continuously heating the bottom of the product tray, the frozen water is gradually and gently sublimated from the solid slurry residues over a period of about 20 hours.
[0094] Using the method of temperature fractionated carbon phase analysis (according to DIN 19539), the sum of the TOC content (temperature-dependent distinction of the total organic carbon) and the TIC content (temperature-dependent distinction of the total inorganic carbon) of the LLZO powder wet-ground in water is determined to be 0.4%, with the carbon detected being mainly inorganic carbon. The moisture content is determined to be 25%.
[0095] e) Production of fine powder from Nb-doped LLZO with residual water removed To reduce the water load and traces of carbonate, the LLZO powder is directly transferred immediately after freeze-drying to a Nabertherm N20 / H type furnace with nitrogen gas flowing through it and baked out at 700° C. for 4 hours.
[0096] After baking, the LLZO powder is removed from the furnace cooled with nitrogen gas flowing through it and vacuum packed directly into bags made of aluminum bonded film.
[0097] Using the method of temperature fractionated carbon phase analysis (according to DIN 19539), the TIC content (temperature-dependent distinction of inorganic total carbon) of the LLZO powder wet-ground in water and freeze-dried in vacuum followed by calcination at 700 °C for 4 h is determined to be 0.10% and the moisture content to be 0.8%.
[0098] For quality control, X-ray diffractograms (XRD) are made on the calcined powder. The resulting XRD is shown in Figure 1. It shows that undesirable extraneous phases, especially lithium-poor phases such as La in pyrochlore, which can lead to a dramatic reduction in conductivity, are not present. 2 Zr 2 O 7 It shows no sign of formation of Nb. It only has reflections of the cubic modification of Nb-doped LLZO.
[0099] 0.4 g of the powder is uniaxially pressed in a steel press mold with a force of 30 kN to produce a green body with a diameter of 10 mm and a thickness of 2-3 mm. The green body is then sintered at 1130 °C for 30 min to densify to a density of 90%. A gold layer is applied to both sides of the specimen and its conductivity is measured at room temperature using electrochemical impedance spectroscopy (EIS). The measured data is then used to determine a conductivity of 6.3 × 10 -4 The conductivity value in S / cm is calculated.
[0100] Example 2 Example of the preparation of a solid lithium ion conductor material that crystallizes based on the garnet structure, on the example of lithium lanthanum zirconium oxide (LLZO) as a powder with little water.
[0101] The production is carried out by the method according to the invention by a high-temperature process in the form of a melting process, natural cooling of the melt, coarse comminution under dry conditions, fine grinding in a steam jet mill and drying N 2This is done through a temperature treatment at 700°C under atmospheric conditions.
[0102] A low water LLZO powder according to Example 2 was prepared as described below:
[0103] a) Preparation of Nb-doped LLZO melt as hot intermediate product The preparation is carried out similarly to Example 1.
[0104] b) Preparation of agglomerated blocks from Nb-doped LLZO as a cold intermediate. The preparation is carried out similarly to Example 1.
[0105] c) Omission of ceramicization The explanation for Example 1 also applies here.
[0106] d) Production of fine powders loaded with residual water from Nb-doped LLZO The following comminution steps are carried out to produce a powder, still loaded with residual water, from the bulk block of Nb-doped LLZO material:
[0107] First, the agglomerated blocks are broken into smaller pieces using hammers and chisels. These are then fed in one or more passes through a jaw crusher until the pieces are a maximum of 10 mm in their longest dimension. These are then crushed in a Fritsch Pulverisette 13 classic disc mill. 99 Grind to a size of <1 μm.
[0108] 5 kg of coarsely ground Nb-doped LLZO powder with a particle size <1 mm is placed in a steam jet mill of the Netzsch s-Jet 25 type. Jet milling is carried out at a pressure of 10 bar using superheated steam as the grinding medium through a ceramic nozzle. Subsequent sieving gives a particle size distribution d after separation on a cassette filter. 50 = 0.9 μm, d 90 = 1.6 μm, and d 99= 2.6 μm. The particle size is measured using a CILAS 1064 type particle sizer using the static light scattering method. The measurements are carried out in water as medium (refractive index: 1.33) and evaluated according to the Mie method (Re = 1.8, Im = 0.8).
[0109] Using the method of temperature fractionated carbon phase analysis (according to DIN 19539), the sum of the TOC and TIC contents of the LLZO powder wet-ground in water is determined to be 5%, with the carbon detected being mostly inorganic carbon. The moisture content is determined to be 5.1%.
[0110] e) Production of fine powder from Nb-doped LLZO with residual water removed To reduce the water load and traces of carbonate, the LLZO powder is directly transferred immediately after freeze-drying to a Nabertherm N20 / H type furnace with nitrogen gas flow through and baked out at 700° C. for 4 hours.
[0111] After baking, the LLZO powder is removed from the furnace cooled with nitrogen gas flowing through it and vacuum packed directly into bags made of aluminum bonded film.
[0112] Using the method of temperature fractionated carbon phase analysis (according to DIN 19539), the TIC content of the LLZO powder wet-ground in water and freeze-dried and then calcined in vacuum at 700 °C for 4 h is determined to be 0.1%. The water content is 0.9%. For quality control, an X-ray diffractogram (XRD) is made of the calcined powder. The resulting X-ray diffractogram is shown in Figure 2. It shows that the undesired lithium-poor phases, e.g. La in pyrochlore, are not present. 0.33 NbO 3 , La 2 Zr 2 O 7 and La 2 O 3 However, the proportion is so small that it only slightly affects conductivity.
[0113] 0.3 g of the powder is uniaxially pressed in a suitable press mold with a force of 30 kN to give a green body with a diameter of 10 mm and a thickness of 2-3 mm. The green body is then sintered at 1130°C for 30 min to a density of 92%. A gold layer is applied to both sides of the sample body and its conductivity is measured at room temperature using electrochemical impedance spectroscopy (EIS). The measured data are then used to determine a conductivity of 2×10 -4 The conductivity value in S / cm is calculated.
[0114] Example 3 Example of the preparation of solid lithium ion conductor materials based on the NASICON structure on the example of lithium aluminum titanium phosphate (LATP) as a powder with little water.
[0115] The preparation can be carried out by the method according to the invention by a high-temperature process in the form of a melting process, quenching of the melt on contact with water, ceramification of the dried granulated particles, coarse comminution of the granulated particles under dry conditions, wet grinding in water with subsequent freeze-drying and drying N 2 This is done through a temperature treatment at 700°C under atmospheric conditions.
[0116] a) Production of green glass melts as hot intermediates for boron-containing LATP 5.5% Li 2 O, 3.7% Al 2 O 3 , 33.1% TiO 2 , and 55.5% P 2 O 5 , and 2.2% B 2 O 3 The starting glass for the final lithium-ion conductive phosphate-based glass ceramic of the composition was melted in an overflow crucible at a temperature of 1650° C. In order to completely homogenize the glass melt, it was kept at a temperature of 1600° C. in a selected melting unit, during which O 2 Gas was allowed to flow through.
[0117] b) Production of granules from boron-containing LATP green glass as a cold intermediate product The glass produced through the melting process is guided in a liquid state (temperature 450°C to 1600°C, viscosity 0.1 to 1 dPa·s) to the "water chute" in a jet. Water is jetted through this water chute at high speed (throughput 0.1 to 3 m 3 / min, preferably 1.7m 3 / min) over an inclined stainless steel channel (angle of inclination 10-75°, preferably 45°). At the bottom, the entire wall of the channel is covered with a water film. When the melt impinges on the flowing water film, the melt jet breaks up into fine droplets. The diameter of the droplets depends on the interval of the melt feed into the chute, the inclination angle of the chute and, in particular, the adjusted water flow rate. The process is carried out in such a way that the diameter is less than 20 mm, preferably less than 10 mm, particularly preferably 0.5-1 mm. The droplets thus do not come into direct contact with the underlying steel material. At the contact point with the water film, a steam cushion is formed, so that direct contact of the glass melt with liquid water at this point is avoided. The droplets then move in a trajectory to a collecting vessel or are swept away by the water jet, where they can bounce off on a cover above the water channel. The droplets solidify either immediately after the melt jet breaks up into droplets or during the flight movement. Upon impact with the wall of the collection vessel or cover, they are already solid, but still very hot (>700 °C) and therefore above the ceramification temperature measured in a DTA measurement (differential thermal analysis). The collection vessel is filled or flushed with a cooling medium (in this case water). Thereby, the (solid) particles are cooled so quickly during immersion that no (or only slightly) crystallization occurs. In this way, almost completely amorphous glass (ceramic) granules are obtained (fraction of crystalline phases by X-ray diffraction evaluated by Rietveld <15%).
[0118] After cooling, the glass frit particles are separated by sieving from the water used as cooling medium and dried in a drying cabinet at 150° C. for 12 hours.
[0119] c) Ceramization of green glass frit particles made of boron-containing LATP To produce the native lithium ion conducting LATP phase with NASICON structure, the dried green glass granule particles are cerammed at 800°C to 980°C for 1 to 12 hours, preferably at 950°C for 6 hours.
[0120] In the process, the residual water of the glass still present is largely expelled from the material. Using the method of temperature fractionated carbon phase analysis (according to DIN 19539), which can also be taken into account for the measurement of grain size, the moisture content is determined to be 0.05%.
[0121] d) Production of fine powders loaded with residual water from boron-containing LATP The following comminution steps are carried out to produce a powder, still loaded with residual water, from glass-ceramic granules made of boron-containing LATP material:
[0122] Firstly, the particles present are brought into a disc mill of the type Pulverisette 13 classic from the company Fritsch, where they are ground to a particle size of <100 μm.
[0123] 1 kg of this coarsely ground boron-containing LATP powder is dispersed in 2.33 L of water using a dissolver, with as few agglomerates as possible. The suspension is then loaded into the reservoir of an agitator ball mill and ground for 2.5 hours using the multi-pass method in a grinding chamber equipped with a pin mill agitator. The grinding chamber is then filled with ZrO 2 The milling is completed when 50% of the particles present in the milling slurry have a diameter of approximately 0.95 μm, 90% have a diameter of approximately 2.43 μm, and 99% have a diameter of approximately 3.86 μm. The particle size is measured using the static light scattering method with a CILAS 1064 type particle sizer. The measurements are carried out in water as medium (refractive index: 1.33) and evaluated according to the Mie method (Re=1.8, Im=0.8).
[0124] After grinding, the ground slurry is subjected to drying in a freeze dryer. For this, it is first poured over a large area into a product tray prepared for its intended use and frozen at a temperature of -30°C. A vacuum corresponding to the value required for the sublimation of the medium is then applied (<6.11 mbar for water). By subsequently continuously heating the bottom of the product tray, the frozen water is gradually and gently sublimated from the solid slurry residues over a period of about 20 hours.
[0125] Using the method of temperature fractionated carbon phase analysis (according to DIN 19539), the sum of the TOC and TIC contents of the LATP powder wet-milled in water is below the detection limit of 0.01%. The moisture content is determined to be 2.5%.
[0126] e) Production of fine powder from boron-containing LATP with removal of residual water To reduce the water load and traces of carbonate, the LATP powder is directly transferred immediately after freeze-drying to a Nabertherm N20 / H type furnace with nitrogen gas flowing through it and baked out at 400° C. for 4 hours.
[0127] After baking, the LATP powder is removed from the nitrogen gas cooled oven and vacuum packed directly into aluminum bonded film bags.
[0128] Using the method of temperature fractionated carbon phase analysis (according to DIN 19539), the TIC content of LATP powder wet-ground in water, freeze-dried and then baked out in vacuum at 400° C. for 4 hours is below the detection limit of 0.01%. The moisture content is 0.7%.
[0129] For quality control, an X-ray diffractogram (XRD) is made on the calcined powder. The resulting X-ray diffractogram is shown in Figure 3. It shows that undesirable foreign phases, especially lithium-poor phases such as AlPO 4 or TiP 2 O 7 It shows no signs of formation of LATP crystals. It has only reflections of LATP crystals.
[0130] 0.3 g of the powder is uniaxially pressed in a suitable press mold with a force of 30 kN to give a green body with a diameter of 10 mm and a thickness of 2-3 mm. The green body is then sintered at 800 °C for 3 hours to densify it to a density of 90%. A gold layer is applied to both sides of the sample body and its conductivity is measured at room temperature using electrochemical impedance spectroscopy (EIS). The measured data are then used to determine a 9 × 10 -4 The conductivity value in S / cm is calculated.
Claims
1. 1. A method for producing a solid lithium ion conductor material comprising the steps of: (1) providing a starting material for a solid-state lithium ion conductor material; (2) Using the starting material of the solid lithium ion conductor material, - Melt method, sintering method, ・Ceramicization method, Calcination of a sol-gel precursor, or Bottom-up synthesis in pulse reactors performing at least one high temperature step, (3) cooling or quenching the resulting hot intermediate product; and (4) performing a cryogenic process in one or more comminuted stages to produce a powder; in step (3) and / or step (4), the respective intermediate product is contacted with water and / or water vapor and subsequently dried, In the low-temperature process according to step (4), the comminution comprises grinding the intermediate product into a powder using water; and Step (4) is followed by step (5), which comprises carrying out a temperature treatment at a temperature of at least 200° C. to remove the residual water remaining in the product obtained, wherein said temperature treatment is carried out in order to remove CO 2 in the absence of an ambient atmosphere, resulting in a powder of solid lithium ion conductor material having a moisture content of less than 1.0 wt. %. The method.
2. The starting material is Materials for producing solid lithium-ion conductor materials based on the NASICON structure, or Materials for the production of solid lithium-ion conductor materials based on garnet structures The method according to claim 1, characterized in that the compound is selected from the group consisting of:
3. The starting material is materials for producing solid lithium-ion conductor materials based on lithium aluminum germanium phosphate (LAGP) and / or based on lithium aluminum titanium phosphate (LATP), or Materials for producing solid lithium ion conductor materials based on lithium lanthanum zirconium oxide (LLZO) The method according to claim 2, characterized in that the compound is selected from the group consisting of:
4. 3. The method according to claim 2, characterized in that the material for producing a solid lithium-ion conductor material based on a garnet structure has an excess of lithium compared to the stoichiometric composition.
5. 4. The method according to claim 3, characterized in that the material for producing a solid lithium-ion conductor material based on lithium lanthanum zirconium oxide (LLZO) has an excess of lithium compared to the stoichiometric composition.
6. In step (3), the hot, still liquid intermediate product is contacted with water and / or water steam and atomized into droplets using a water nozzle or water chute; and In step (3), the diameter of the droplets of the liquid intermediate product is controlled by using a water chute and varying the interval of the melt feed to the water chute, the inclination angle of the water chute in the range of 10 to 75°, and the inclination angle of the water chute in the range of 0.1 to 3 m. 3 6. The method according to claim 1 , characterized in that the flow rate of the water is adjusted to less than 20 mm depending on the adjusted water flow rate in the range of 1 / min.
7. 7. The method according to claim 1, characterized in that after step (3) and before step (4), an intermediate step is carried out which comprises a heat treatment using a defined temperature-time program of heating, holding and cooling, each optionally with an intermediate holding step, in order to adjust the cooled intermediate product to the desired crystal structure.
8. 8. The method according to claim 7, characterized in that the intermediate steps are repeatedly carried out to adjust the desired crystalline phase composition and crystalline proportion.
9. 2. The method of claim 1, wherein step (5) is carried out at a temperature of at least 300°C.
10. In a low temperature process according to step (4), the crude product is converted into a powder form having a desired particle size and particle size distribution, which process comprises one or more of the following steps: - Subdivision using hammers and chisels; Compression using roll crushers and / or jaw crushers; comminution using ball mills and / or hammer mills; comminution using ball mills, impact mills and / or planetary mills; - Comminuted using a disc vibratory mill, Comminuted using counter jet mills, spiral jet mills and / or steam jet mills; comminution using a dry ball mill and / or a wet ball mill, comminution using a dry mixer ball mill and / or a wet mixer ball mill, - High-energy comminution in a high-speed rotor ball mill 10. The method according to claim 1, further comprising:
11. 11. Use of a solid lithium ion conductor material in powder form obtainable by the method according to any one of claims 1 to 10 in a battery or accumulator.
Citation Information
Patent Citations
Lithium ion secondary battery and solid electrolyte
JP2007066703A
Manufacturing method of lithium ion secondary battery
JP2009206090A
Method for restoring ion conductivity of solid electrolyte ceramic material
JP2013219017A
Lithium-containing garnet type oxide
JP2017061397A
Lithium ion conductive composite material containing at least one polymer and lithium ion conductive particle, and manufacturing method of lithium ion conductive body from composite material
JP2019102460A